A Pug's Head - Asimovic, J. (Tufts Archival Research Center, 2025)
Tissue paper and glue. Art created as part of Project PAINT, in association with the Richard J. Donovan Correctional Facility in San Diego, and California State Prison- Centinela in Imperial, California.